Immunological study of candidiasis in women using intrauterine contraceptive devices in Erbil city - Roaa Muhmmed Yahya; Bashar Sadeq Noomi; Hiba younis Khalaf (Zien Journals, 2022)
Among 80 samples of vaginal swabs taken from female patients at a Maternity Teaching Hospital in Erbil city for the period between May and November 2021 complained of valvovaginitis symptoms, including both intrauterine contraceptive devices (IUCD) and non-intrauterine contraceptive users. The vaginal samples from patients were culture on Sabouraud Dextrose Agar (SDA) and species identification utilizing Chrom agar. The highest incidence rate had discovered in age group of 26-35 years 17(54.84%), followed by >36 years 8(25.81%), and the lowest rates was observed
Keywords: Candida species; CHROM agar; TLR4; Dectin-1